Early Childhood Health - Mills, Dora (Maine Policy Review, 2009)
Dr. Dora Anne Mills presents a panoramic portrait of early childhood health in Maine, describing the ways in which poverty, health insurance, pregnancy, early growth and development, infectious and chronic diseases, oral health, environmental health, injury, mental health and physical activity and nutrition affect children. She notes policy successes in these areas and describes some of the challenges that remain and the new challenges that are arising.